Are Multiple Repeated Cesarean Sections Really as Safe? (Latakia University Journal -Medical Sciences Series, 2021)
Cesarean delivery rates have risen in Syria, as well all globally, in recent years. In our country, their prevalence is 16-27%. Surgical complications were compared between patients with three or less prior cesarean deliveries and four or more prior cesarean deliveries. Records of 120 patients who had undergone cesarean sections in our Department of Obstetrics and Gynecology, between August and November 2019, were retrospectively studied. Cases were reviewed on the basis of age, type of operation, type of anesthesia, number of cesarean sections, time of hospitalization, and intra-operative and postoperative complications.Cesarean sections had been performed on 62 (51.7%) patients whose cesarean number was three or less, while 58 (48.3%) patients had multiple cesarean sections four or more.There is no greater risk of maternal complications in patients with four or more prior cesareans, excepting intra-abdominal adhesions.